Impact of the Mediterranean Diet on stroke incidence and cognitive impairment in CADASIL and CAA patients: the DIETETICA study - Strazzabosco, Camilla; Storti, Benedetta; Marinoni, Giulia; Carolina, De Toma; Canavero, Isabella; Rifino, Nicola; Boncoraglio, Giorgio; Zacarias, Esteban; Francia, Alessandro; Pollaci, Giuliana; Carrozzini, Tatiana; Potenza, Antonella; et al. (Frontiers in Nutrition, 2025)
IntroductionCerebral small vessel disease (cSVD), including Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) and Cerebral Amyloid Angiopathy (CAA), is a major cause of non-sporadic stroke and cognitive impairment. Despite the recognized benefits of the Mediterranean Diet (MD) on cardiovascular and neurodegenerative diseases, its role in cSVD has not been yet investigated.MethodsThe DIETETICA study (“Effect of Mediterranean Diet on stroke incidence and cognitive impairment in patients with CADASIL and CAA”) aims to explore the association between MD adherence, stroke incidence and cognitive impairment in patients affected by CADASIL and CAA. During observational phase, 22 participants were recruited: 9 with CADASIL and 13 with CAA. 68.18% were male and 31.82% were female.ResultsAccording to the response obtained through a validated 14-item questionnaire, 63.63% of the total cohort had moderate adherence to MD, 27.27% had low adherence, and 9.09% had high adherence. Differences in body composition, in terms of fat mass (FM) and fat-free mass (FFM), were observed between the two patient cohorts. Overall, the preliminary observations regarding dietary daily intake were characterized by inadequate of nutrients which are known to have neurovascular benefits, such as polyunsaturated fatty acids (PUFAs), calcium, potassium and vitamin D, for both CADASIL and CAA patients.ConclusionThe present study will pave the way to the evaluation of the effects of MD pattern on cSVD, in order to provide evidence-based dietary recommendations aimed at reducing stroke incidence and cognitive impairment.